Introduction to unmanned aircraft systems - Marshall, Douglas M., 1947-; Barnhart, Richard K.; Shappee, Eric, 1968-; Most, Michael (CRC Press, 2016)
"Introduction to Unmanned Aircraft Systems surveys the fundamentals of unmanned aircraft system (UAS) operations, from sensors, controls, and automation to regulations, safety procedures, and human factors. It is designed for the student or layperson and thus assumes no prior knowledge of UASs, engineering, or aeronautics. Dynamic and well-illustrated, the first edition of this popular primer was created in response to a need for a suitable university-level textbook on the subject. Fully updated and significantly expanded, this new Second Edition: Reflects the proliferation of technological capability, miniaturization, and demand for aerial intelligence in a post-9/11 world, Presents the latest major commercial uses of UASs and unmanned aerial vehicles (UAVs), Enhances its coverage with greater depth and support for more advanced coursework, Provides material appropriate for introductory UAS coursework in both aviation and aerospace engineering programs. Introduction to Unmanned Aircraft Systems, Second Edition capitalizes on the expertise of contributing authors to instill a practical, up-to-date understanding of what it takes to safely operate UASs in the National Airspace System (NAS). Complete with end-of-chapter discussion questions, this book makes an ideal textbook for a first course in UAS operations. An instructor's manual is available with qualifying course adoption"--The publisher